2019
DOI: 10.1002/ejsp.2617
|View full text |Cite
|
Sign up to set email alerts
|

Reaping the benefits of cultural diversity: Classroom cultural diversity climate and students’ intercultural competence

Abstract: Culturally diverse schools may constitute natural arenas for training crucial intercultural skills. We hypothesized that a classroom cultural diversity climate fostering contact and cooperation and multiculturalism, but not a climate fostering color‐evasion, would be positively related to adolescents’ intercultural competence. Adolescents in North Rhine‐Westphalia (N = 631, Mage = 13.69 years, 49% of immigrant background) and Berlin (N = 1,335, Mage = 14.69 years, 52% of immigrant background) in Germany report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 92 publications
10
60
0
3
Order By: Relevance
“…One of the important contributions of the present study is that it draws attention to the importance of classroom context in understanding the factors that may contribute to adolescents' engagement in ethnic victimization. Supporting the premises of social norms theories (Perkins and Berkowitz 1986) and previous research (e.g., Schachner et al in press;Schwarzenthal et al 2019), the current findings suggest that, when adolescents perceive that students in their classroom are open to diverse views, respect each other's cultural values, and cooperate with each other on different class activities, they are less likely to engage in ethnic victimization. Importantly and interestingly, the effect of perceived positive contact norms on engagement in ethnic victimization is the same among youth with different attitudes and feelings toward immigrants, even after controlling for certain demographic factors, such as gender, immigrant status, and classroom ethnic composition.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…One of the important contributions of the present study is that it draws attention to the importance of classroom context in understanding the factors that may contribute to adolescents' engagement in ethnic victimization. Supporting the premises of social norms theories (Perkins and Berkowitz 1986) and previous research (e.g., Schachner et al in press;Schwarzenthal et al 2019), the current findings suggest that, when adolescents perceive that students in their classroom are open to diverse views, respect each other's cultural values, and cooperate with each other on different class activities, they are less likely to engage in ethnic victimization. Importantly and interestingly, the effect of perceived positive contact norms on engagement in ethnic victimization is the same among youth with different attitudes and feelings toward immigrants, even after controlling for certain demographic factors, such as gender, immigrant status, and classroom ethnic composition.…”
Section: Discussionsupporting
confidence: 86%
“…Two alternative explanations can be proposed for this finding. As previously mentioned, being in an inclusive and socially cohesive classroom may contribute to the development of intercultural competence and awareness among adolescents (Schwarzenthal et al 2019) and foster crossethnic friendships (Schachner et al 2015). Such competence and inter-personal relationships may help adolescents embrace differences rather than perceive them as a threat, and, in turn, may prevent the occurrence of incidents of ethnic victimization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The stressing similarities ideology acknowledges cultural differences but emphasizes common ground, what is shared between individuals ("We are all humans") and the necessity of treating everyone equally (Rosenthal and Levy 2010). School climate research has shown consistently that the stressing similarities ideology remains the dominant approach reflected in the school curriculum, particularly in Germany (Civitillo 2017; Schachner 2019; Schwarzenthal et al 2020). The emphasis on stressing similarities may be linked to the unique socio-historical context of Germany.…”
Section: The Stressing Similarities Ideologymentioning
confidence: 99%
“…In the case of adolescents in multicultural school settings, there is some evidence which suggests that negative emotions toward peers, such as anxiety, and the orientation to violence are related to a decrease of intercultural competences (Oyeleke et al, 2018;Bagci et al, 2020). A study conducted in Germany by Schwarzenthal et al (2020) also reported that changes in students' cultural competences depend on school climate, in terms of the endorsement of positive attitudes toward multiculturality and the promotion of contact and cooperation.…”
Section: Introductionmentioning
confidence: 99%